Violation of Grice's cooperative maxims in buying and selling interactions at Rangkasbitung Market: A pragmatic study - Dase Erwin Juansah; Pitri Ayuningsih; Robita Ika Annisa (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
Buying and selling interactions in traditional markets involve communication practices such as negotiation, persuasion, and social bonding where speakers do not always adhere to Grice’s Cooperative Principle. While research on Grice’s Cooperative Principle in such interactions is extensive, most studies focus on identifying instances of adherence to or violation of maxims without elucidating the pragmatic functions of these violations within the linguistically diverse socio cultural context of traditional markets. Therefore, this study aims to describe the forms of violations of Grice’s cooperative maxims and explain their pragmatic functions during buying and selling interactions at Rangkasbitung Market. A qualitative descriptive method with a pragmatic approach was employed. The data consisted of utterances from sellers and buyers containing violations of the cooperative maxims. Data collection involved observation specifically listening, nonparticipatory observation, recording, and note-taking while data analysis utilized the extralingual matching method, taking the utterance context into account. The results identified 26 violations of the cooperative maxims: 11 violations of the Maxim of Quantity, 4 of the Maxim of Quality, 2 of the Maxim of Relevance, and 9 of the Maxim of Manner. The findings reveal that maxim violations do not merely reflect communication ineffectiveness; rather, they serve as pragmatic strategies used by sellers and buyers to negotiate prices, persuade interlocutors, maintain bargaining positions, attract buyers' attention, and preserve social relationships during transactions. The novelty of this study lies in its explanation of the strategic functions of maxim violations within the buying and selling interactions at Rangkasbitung Market, which take place in a multilingual community using Indonesian, Sundanese, and a mixture of both. These findings extend the application of Grice’s Cooperative Principle to the context of local economic communication and imply that maxim violations should be understood as communication strategies influenced by interaction goals, social contexts, and culture rather than simply as deviations from conversational norms.